2009
DOI: 10.1176/appi.psy.50.5.500
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Completion Rates and Sustained Viral Response in Hepatitis C Patients With and Without Preexisting Major Depressive Disorder

Abstract: Patients with MDD can be safely and effectively treated with antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…A prospective study (n = 394) analyzed the relationship between baseline and new-onset depression and treatment outcomes, and SVR rates did not differ between patients who developed MDD and those who did not (6). Results from our retrospective cohort study support and extend these findings by comparing rates of antiviral therapy completion and SVR between patients with HCV and MDD versus those without MDD (7). We found that the MDD group had completion and SVR rates similar to patients without MDD.…”
supporting
confidence: 63%
“…A prospective study (n = 394) analyzed the relationship between baseline and new-onset depression and treatment outcomes, and SVR rates did not differ between patients who developed MDD and those who did not (6). Results from our retrospective cohort study support and extend these findings by comparing rates of antiviral therapy completion and SVR between patients with HCV and MDD versus those without MDD (7). We found that the MDD group had completion and SVR rates similar to patients without MDD.…”
supporting
confidence: 63%
“…As a result of this productivity and new information, we now know that patients with diagnoses of major depressive disorder should not necessarily be excluded from treatment [54]. Screening and monitoring of neuropsychiatric symptoms during the course of therapy are strongly recommended[2,55].…”
Section: Discussionmentioning
confidence: 99%
“…Although HCV is treatable in some patients, there is no vaccine and the current treatment [ i.e ., combination therapy with pegylated interferon-alpha (IFN-α) and ribavirin] has only limited efficacy. Sustained viral response (SVR) is typically achieved in only about 40–50% of those with HCV genotype 1 and 75–80% of those with HCV genotypes 2/3[2]. Thus, considerable effort has been devoted to identifying predictors of viral clearance for patients with HCV.…”
Section: Introductionmentioning
confidence: 99%